Discourse and Racism in Hidden Figures - Nur Rachmatiya Rosa Zahra; Rasiah (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
Abstract This research aims to describe discourse and racism in the Hidden Figures movie using discourse and racism theory based on Dijk’s approach. The results showed that the ten aspects of Dijk's theory of discourse and racism could be found in several characters such as speech, expressions, and actions that refer to the use of discourse and racism in the Hidden Figures movie. There are two aspects of discourse and racism that are most dominantly depicted in this movie, namely aspects of nonverbal structure and aspects of syntax. In the nonverbal structure aspect, the visible form of racism is the depiction of facial expressions such as anger, annoyance and dislike as well as body movements refusing to interact for a long time with black people. Discourse and racism in the Hidden Figures movie also display racist behavior towards black people as a reflection of a system of prejudice, namely negative emotional reactions and stereotypes, namely judgments or assumptions based on groups and people's characteristics. This is illustrated by the experiences of Katherine, Dorothy and Mary regarding the separation of public facilities such as toilets, libraries and education. Keywords: discourse and racism, hidden figures, prejudice, stereotype